Effects of gamma oryzanol and proanthocyanidin from purple glutinous rice bran (Oryza sativa L.) on antibody production and oxidative status in oxidative stress BALB/c mice - Punyatong M. (2014)
Gamma oryzanol (GO) and proanthocyanidin (PA) are antioxidants of purple glutinous rice bran (Oryza sativa L.). Both antioxidants give positive effects on health as "Functional Food". The objective of this study was determined the effect of oral-fed antioxidant substances of purple glutinous rice (Oryza sativa L.) on antibody production and oxidative status in oxidative stress BALB/c mice. The experiment was divided into two steps. One was in vitro test: to find out the equilibrium activity between oxidant (rancid rice bran oil, RO) and antioxidants (GO and PA). Two was in vivo test: to measure the antibody value and oxidative status in BALB/c mice which intake equilibrium ratios of oxidant to antioxidants from in vitro test. The in vitro test has shown equilibrium activity between oxidant to antioxidants, RO:GO at 1:0.8 ratio (antioxidant level after reacted with oxidant = 2.514 ± 0.838 μM/mg) and RO:PA at 1:0.6 ratio (antioxidant level after reacted with oxidant = 13.768 ± 0.785 μM/mg). The in vivo test gave that the IgG and IgM level were decreased (p<0.05) when fed only RO but increased to initial normal levels when fed RO plus GO or PA. Also in glutathione (GSH) and malondialdehyde (MDA) level in blood which had related results with antibody levels (p<0.05). In conclusion, supplemented antioxidant substances of purple glutinous rice to the oxidative stress mice at equilibrium ratios could recover the antibody level and balancing of oxidative status in the body to normal status. It can be concluded that GO and PA of purple glutinous rice display the beneficial effect to the health and can used for "Functional Food" to improving the oxidative stress.